A modified lithium-ion battery cathode slurry, its preparation method and application

By introducing Na ions into the positive electrode slurry of lithium-ion batteries to form a stable transition phase, the problem of unstable redox reaction of lithium manganese iron phosphate positive electrode material under high voltage is solved, thus improving the cycle and storage performance of the battery cell.

CN115863652BActive Publication Date: 2026-11-03BATTERO TECH CORP LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211715175.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2026-11-03
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

Existing technologies are insufficient to effectively improve the stability of redox reactions of lithium iron manganese phosphate (LFMP) cathode materials under high voltage, resulting in poor cycle performance and storage performance.

Method used

Introducing Na ions, which have a larger radius than Li ions, into the positive electrode slurry of lithium-ion batteries enhances the stability of the redox reaction of the positive electrode active material under high voltage by forming a stable transition phase. The combination of organic or inorganic sodium sources and binders optimizes ion exchange and crystal structure.

Benefits of technology

It significantly improves the cycle performance and storage performance of the battery cell, and enhances the stability of the redox reaction of the positive electrode active material under high voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004027602320000141
    Figure BDA0004027602320000141
Patent Text Reader

Abstract

The application provides a modified lithium ion battery positive electrode slurry as well as a preparation method and application thereof, the positive electrode slurry comprising a positive electrode active material, a conductive agent, a sodium source and a solvent; and the mass fraction of the organic sodium source is 0.5-10% in the total dry base mass of the positive electrode slurry, taken as 100%. The application introduces Na ions with a larger ionic radius than Li ions by adding the organic sodium source in the positive electrode slurry, effectively improves the reaction energy level of the positive electrode active material, improves the stability of the positive electrode active material in the electrochemical reaction under high voltage, and makes the prepared battery cell obtain excellent cycle and storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery cathode technology, specifically relating to a modified lithium-ion battery cathode slurry, its preparation method, and its application. Background Technology

[0002] Lithium iron manganese phosphate (LiFeMnPO4, LFMP) cathode material is the next-generation cathode material of existing lithium iron phosphate (LiFePO4, LFP). Its biggest difference from LFP lies in the substitution of some Fe ions with Mn ions in its crystal structure. This change not only increases the operating voltage of the LFMP cathode (2.0-4.3V) but also alters the conduction kinetics of Li ions in the cathode material. Therefore, LFMP has a higher capacity and higher capacity retention rate than LFP, with significantly improved low-temperature performance. However, LFMP has a fatal drawback: the redox reaction at higher voltages, dominated by a manganese platform, results in the loss of reactive oxygen species. This causes the transition metal to be in a metastable state during the redox reaction, significantly reducing the cycle performance of LFMP and greatly impacting the storage performance of the battery cell.

[0003] Regarding the issue of reaction stability in LFMP under high voltage, current solutions mainly fall into two categories. The first category involves coating the surface of LFMP, primarily including coating the LFMP surface with pure carbon or inorganic oxide materials. The methods used are mainly liquid-phase and solid-phase methods. For example, CN107768613A discloses a method for preparing carbon-coated lithium manganese iron phosphate, which includes the following steps: (1) dissolving phosphate salts, manganese salts, iron salts, lithium salts, and reducing agents in water, and then mixing them evenly with an organic solvent, followed by a solvothermal reaction to obtain lithium manganese iron phosphate nanomaterials; (2) mixing the lithium manganese iron phosphate nanomaterials and a carbon source evenly, and then performing high-temperature heat treatment under gas protection to obtain carbon-coated lithium manganese iron phosphate. CN115172718A discloses a method for preparing lithium manganese iron phosphate by solid-phase coating, which includes the following steps: ball milling lithium manganese iron phosphate, paraffin wax, and a dispersant at above 40°C until evenly mixed, followed by cooling to obtain a mixture; calcining the mixture to obtain carbon-coated lithium manganese iron phosphate.

[0004] The second type involves doping the surface of LFMP, mainly including doping with elements such as Ti, Cr, or Mg. For example, CN115332516A discloses a magnesium-nickel co-doped lithium manganese iron phosphate cathode material and its preparation method. The preparation method includes the following steps: S1, dissolving lithium source, phosphorus source, iron source, manganese source, magnesium source, and nickel source in a solvent and stirring continuously, adding carbon source dropwise until it is stirred into a gel; S2, drying the gel mixture to obtain a dry gel; S3, calcining the dry gel in a protective atmosphere to obtain a carbon-coated magnesium-nickel co-doped lithium manganese iron phosphate cathode material.

[0005] The main purpose of both methods is to lower the Fermi level of LFMP in redox reactions, making it more stable and thus improving the cycle and storage performance of the battery cell. However, currently, these two mainstream technologies do not seem to significantly improve the cycle and storage performance of LFMP. The main reason is that modifying LFMP by coating or doping is primarily aimed at improving the electrochemical kinetics of the battery cell during charge and discharge. However, LFMP itself is unstable and participates in electrochemical reactions, making these coating or doping methods not particularly effective in solving the stability problem of redox reactions.

[0006] Therefore, improving the redox stability of positive electrode active materials under high voltage in electrochemical reactions is an urgent technical problem to be solved. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a modified lithium-ion battery cathode slurry, its preparation method, and its applications. By adding a sodium source to the cathode slurry, the present invention introduces Na ions, which have a larger ionic radius than Li ions. This effectively improves the reaction energy level of the cathode active material and enhances the stability of the cathode active material under high voltage redox reactions during electrochemical reactions, resulting in a battery cell with excellent cycle and storage performance.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a modified lithium-ion battery cathode slurry, the cathode slurry comprising a cathode active material, a conductive agent, a sodium source, and a solvent;

[0010] Based on the total dry weight of the positive electrode slurry as 100%, the mass fraction of the sodium source is 0.5-10%, for example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0011] In this invention, Na ions, which have a larger ionic radius than Li ions, are introduced into the positive electrode slurry. This allows Na ions to occupy the sites occupied by Li ions during the electrochemical reaction, thereby forming a more stable transition phase. The presence of this stable transition phase makes the redox reaction of the positive electrode active material more stable under high voltage, and the active oxygen bonding during the phase transition process is stronger, which can significantly improve the cycle and storage performance of the battery cell.

[0012] In this invention, if the mass fraction of sodium source is too low, the interaction between Na ions and Li ions is weak, and bonding and energy level exchange between the two ions cannot be achieved; if the mass fraction of sodium source is too high, on the one hand, sodium will occupy more Li vacancies, hindering the insertion and extraction of lithium ions; on the other hand, it will have a certain impact on the crystal structure of the phase, and the energy level and lattice stress will change, thereby affecting the cycle performance of the cell.

[0013] Preferably, the sodium source includes an organic sodium source or an inorganic sodium source;

[0014] Preferably, the organic sodium source includes any one or a combination of at least two of carboxymethyl cellulose, tetrasodium ethylenediaminetetraacetate, or disodium ethylenediaminetetraacetate, with tetrasodium ethylenediaminetetraacetate being the most preferred.

[0015] Preferably, the inorganic sodium source includes Na2CO3 and / or NaHCO3.

[0016] Preferably, the modified lithium-ion battery cathode slurry also includes a binder.

[0017] Preferably, the adhesive comprises any one or a combination of at least two of polyvinylidene fluoride, polyacrylonitrile, or polyacrylic acid, with polyacrylonitrile being the most preferred.

[0018] In this invention, polyacrylonitrile is preferably used as a binder, which has a certain interaction with the sodium source at the ionic level.

[0019] Preferably, the mass ratio of the binder to the sodium source is (0.5-10):(0.5-8), wherein the binder is selected from a range of 0.5-10, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, and the sodium source is selected from a range of 0.5-8, for example, 0.5, 1, 2, 3, 4, 5, 6, 7 or 8.

[0020] Preferably, based on the total mass of the positive electrode active material, conductive agent, binder, and sodium source being 100%, the mass fraction ratio of the positive electrode active material, conductive agent, binder, and sodium source is (80-90)%:(2-9)%:(0.5-10)%:(0.5-8)%, wherein the positive electrode active material is selected within the range of (80-90)%, for example, it can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89 ... The conductive agent can be selected from 2% to 90%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, or 9%. The binder can be selected from 0.5% to 10%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%. The sodium source can be selected from 0.5% to 8%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0021] Preferably, the positive electrode active material includes any one or a combination of at least two of lithium manganese iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, or lithium cobalt manganese oxide.

[0022] Preferably, the conductive agent includes any one or a combination of at least two of carbon nanotubes, carbon black, graphene, or conductive graphite.

[0023] Preferably, the solvent comprises N-methylpyrrolidone and / or N-dimethylformamide.

[0024] In a second aspect, the present invention provides a method for preparing a modified lithium-ion battery cathode slurry as described in the first aspect, the method comprising:

[0025] The modified lithium-ion battery positive electrode slurry is obtained by mixing the positive electrode active material, conductive agent, organic sodium source and solvent.

[0026] Preferably, the mixing temperature is 25-55°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C or 55°C.

[0027] Preferably, the mixing order is as follows:

[0028] (1) Dry-mix the positive electrode active material, conductive agent and sodium source to obtain a dry mixture;

[0029] (2) Disperse the dry mixture from step (1) in a solvent to obtain the modified lithium-ion battery cathode slurry.

[0030] Preferably, the dry mixing in step (1) is performed using a dual planetary dispersion mixer.

[0031] In this invention, a dual planetary dispersing mixer is used for mixing and dispersing, resulting in high uniformity and high production efficiency.

[0032] Preferably, the dry mixing rate is 1000-2000 rpm, for example, it can be 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm or 2000 rpm.

[0033] In this invention, if the rate is too low, the dispersion will be uneven; if the rate is too high, the temperature will rise and the shear force will be too high, causing the adhesive polymer to lose its adhesiveness.

[0034] Preferably, the dry mixing time is 15-45 minutes, for example, it can be 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or 45 minutes.

[0035] Preferably, the dispersion process in step (2) is accompanied by stirring.

[0036] As a preferred technical solution, the preparation method includes the following steps:

[0037] (I) The positive electrode active material, conductive agent, binder and sodium source are ball-milled and mixed at 25-55℃ to obtain a dry mixture;

[0038] The mass fraction ratio of the positive electrode active material, conductive agent, binder and sodium source is (80-90)%:(2-9)%:(0.5-10)%:(0.5-8)%, the dry mixing rate is 1000-2000 rpm, and the dry mixing time is 15-45 min.

[0039] (II) The dry mixture described in step (I) is dispersed in a solvent to obtain the modified lithium-ion battery cathode slurry.

[0040] Thirdly, the present invention provides a positive electrode sheet, which is obtained by coating the modified lithium-ion battery positive electrode slurry described in the first aspect onto a current collector and drying it.

[0041] Fourthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising a positive electrode as described in the third aspect.

[0042] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] This invention introduces Na ions, which have a larger ionic radius than Li ions, into the positive electrode slurry. This allows Na ions to occupy the sites occupied by Li ions during the electrochemical reaction, thereby forming a more stable transition phase. The presence of this stable transition phase makes the redox reaction of the positive electrode active material more stable under high voltage, and the active oxygen bonding during the phase transition process is stronger, which can significantly improve the cycle and storage performance of the battery cell. Detailed Implementation

[0045] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0046] Example 1

[0047] This embodiment provides a modified lithium-ion battery cathode slurry, the cathode slurry comprising a cathode active material, a conductive agent, a sodium source, and a solvent;

[0048] The positive electrode active material is lithium manganese iron phosphate, the conductive agent is carbon nanotubes, the sodium source is carboxymethyl cellulose, and the solvent is N-methylpyrrolidone.

[0049] Based on a dry basis total mass of 100% in the positive electrode slurry, the mass fraction of the carboxymethyl cellulose is 5%.

[0050] This embodiment also provides a method for preparing a modified lithium-ion battery cathode slurry, the preparation method comprising the following steps:

[0051] (1) At 40°C, lithium manganese iron phosphate, carbon nanotubes and carboxymethyl cellulose were dry-mixed at 1500 rpm for 30 min using a double planetary mixer to obtain a dry mixture.

[0052] (2) Disperse the dry mixture from step (1) in N-methylpyrrolidone to obtain the modified lithium-ion battery cathode slurry.

[0053] Example 2

[0054] This embodiment provides a modified lithium-ion battery cathode slurry, the cathode slurry comprising a cathode active material, a conductive agent, a sodium source, and a solvent;

[0055] The positive electrode active material is lithium manganese iron phosphate, the conductive agent is conductive graphite, the sodium source is disodium ethylenediaminetetraacetate, and the solvent is N,N-dimethylformamide.

[0056] Based on a dry basis of 100% of the total dry mass of the positive electrode slurry, the disodium ethylenediaminetetraacetate has a mass fraction of 10%.

[0057] This embodiment also provides a method for preparing a modified lithium-ion battery cathode slurry, the preparation method comprising the following steps:

[0058] (1) At 30°C, lithium manganese iron phosphate, conductive graphite and disodium ethylenediaminetetraacetate were dry-mixed at 1000 rpm for 45 min using a double planetary mixer to obtain a dry mixture.

[0059] (2) Disperse the dry mixture from step (1) in NN-dimethylformamide to obtain the modified lithium-ion battery cathode slurry.

[0060] Example 3

[0061] This embodiment provides a modified lithium-ion battery cathode slurry, the cathode slurry comprising a cathode active material, a conductive agent, a binder, a sodium source, and a solvent;

[0062] The positive electrode active material is lithium nickel manganese oxide, the conductive agent is graphene, the binder is polyvinylidene fluoride, the sodium source is Na2CO3, and the solvent is N-methylpyrrolidone. The mass ratio of polyvinylidene fluoride to Na2CO3 is 5:0.5.

[0063] Based on the total mass of the positive electrode active material, conductive agent, binder and sodium source as 100%, the mass fraction ratio of lithium nickel manganese oxide, graphene, polyvinylidene fluoride and Na2CO3 is 89.5%:5%:5%:0.5%.

[0064] This embodiment also provides a method for preparing a modified lithium-ion battery cathode slurry, the preparation method comprising the following steps:

[0065] (1) At 50°C, lithium nickel manganese oxide, graphene, polyvinylidene fluoride and Na2CO3 were dry-mixed at 2000 rpm for 15 min using a double planetary mixer to obtain a dry mixture.

[0066] (2) Disperse the dry mixture from step (1) in N-methylpyrrolidone to obtain the modified lithium-ion battery cathode slurry.

[0067] Example 4

[0068] This embodiment provides a modified lithium-ion battery cathode slurry, the cathode slurry comprising a cathode active material, a conductive agent, a binder, a sodium source, and a solvent;

[0069] The positive electrode active material is lithium nickel cobalt manganese oxide, the conductive agent is carbon black, the binder is polyacrylic acid, the sodium source is NaHCO3, the solvent is N,N-dimethylformamide, and the mass ratio of the polyacrylic acid to the NaHCO3 is 5:2.5.

[0070] Based on the total mass of the positive electrode active material, conductive agent, binder and sodium source as 100%, the mass fraction ratio of lithium nickel cobalt manganese oxide, carbon black, polyacrylic acid and NaHCO3 is 87.5%:5%:5%:2.5%.

[0071] This embodiment also provides a method for preparing a modified lithium-ion battery cathode slurry, the preparation method comprising the following steps:

[0072] (1) At 25°C, lithium nickel cobalt manganese oxide, carbon black, polyacrylic acid and NaHCO3 were dry-mixed at 1500 rpm for 30 min by a double planetary mixer to obtain a dry mixture.

[0073] (2) Disperse the dry mixture from step (1) in NN-dimethylformamide to obtain the modified lithium-ion battery cathode slurry.

[0074] Example 5

[0075] This embodiment provides a modified lithium-ion battery cathode slurry, the cathode slurry comprising a cathode active material, a conductive agent, a binder, a sodium source, and a solvent;

[0076] The positive electrode active material is lithium manganese iron phosphate, the conductive agent is carbon nanotubes, the binder is polyvinylidene fluoride, the sodium source is carboxymethyl cellulose, and the solvent is N-methylpyrrolidone. The mass ratio of polyvinylidene fluoride to carboxymethyl cellulose is 5:5.

[0077] Based on the total mass of the positive electrode active material, conductive agent, binder and sodium source as 100%, the mass fraction ratio of lithium nickel cobalt manganese oxide, carbon nanotubes, polyvinylidene fluoride and carboxymethyl cellulose is 85%:5%:5%:5%.

[0078] This embodiment also provides a method for preparing a modified lithium-ion battery cathode slurry, the preparation method comprising the following steps:

[0079] (1) At 55°C, lithium nickel cobalt manganese oxide, carbon nanotubes, polyvinylidene fluoride and carboxymethyl cellulose were dry-mixed at 1700 rpm for 20 min using a double planetary mixer to obtain a dry mixture.

[0080] (2) Disperse the dry mixture from step (1) in N-methylpyrrolidone to obtain the modified lithium-ion battery cathode slurry.

[0081] Example 6

[0082] The difference between this embodiment and Embodiment 1 is that the sodium source in this embodiment is tetrasodium ethylenediaminetetraacetate.

[0083] The remaining preparation methods and parameters are consistent with those in Example 1.

[0084] Example 7

[0085] The difference between this embodiment and Embodiment 3 is that the adhesive in this embodiment is polyacrylonitrile.

[0086] The remaining preparation methods and parameters are consistent with those in Example 3.

[0087] Example 8

[0088] The difference between this embodiment and embodiment 1 is that the dry mixing method described in step (1) is replaced by mechanical stirring.

[0089] The remaining preparation methods and parameters are consistent with those in Example 1.

[0090] Example 9

[0091] The difference between this embodiment and embodiment 1 is that the temperature during dry mixing in step (1) is 20°C.

[0092] The remaining preparation methods and parameters are consistent with those in Example 1.

[0093] Example 10

[0094] The difference between this embodiment and embodiment 1 is that the temperature of the dry mixing in step (1) is 60°C.

[0095] The remaining preparation methods and parameters are consistent with those in Example 1.

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 5 is that the mass fraction of carboxymethyl cellulose is 0.3%, and the mass fraction ratio of lithium nickel cobalt manganese oxide, carbon nanotubes, polyvinylidene fluoride and carboxymethyl cellulose is 89.7%:5%:5%:0.3%.

[0098] The remaining preparation methods and parameters are consistent with those in Example 5.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 5 is that the mass fraction of carboxymethyl cellulose is 15%, and the mass fraction ratio of lithium nickel cobalt manganese oxide, carbon nanotubes, polyvinylidene fluoride and carboxymethyl cellulose is 75%:5%:5%:15%.

[0101] The remaining preparation methods and parameters are consistent with those in Example 5.

[0102] Comparative Example 3

[0103] The difference between this comparative example and Example 5 is that carboxymethyl cellulose is not added, and the mass fraction ratio of lithium nickel manganese oxide, graphene and polyvinylidene fluoride is 90%:5%:5%.

[0104] The remaining preparation methods and parameters are consistent with those in Example 5.

[0105] Application Example 1

[0106] This application example provides a method for preparing a positive electrode sheet, the method comprising the following steps:

[0107] (1) The modified lithium-ion battery cathode slurry provided in Example 1 was coated on both sides of a copper foil with a thickness of 13 μm. The areal density was controlled to be 24 mg / cm³ during the coating process. 2 Meanwhile, a 20mm electrode area is reserved on both sides;

[0108] (2) The coated electrode is passed through a 20-meter-long oven at 110°C at a speed of 3 m / s to remove the solvent and obtain a positive electrode.

[0109] (3) Roll the positive electrode sheet with a roller press to achieve a compaction density of 2.85 g / cm³. 3 Then, laser cutting is used to divide the electrode roll into two equal rolls, and finally, a mold is used to cut it into a positive electrode sheet that is 60cm long and 30cm wide to complete the production.

[0110] Application Example 2

[0111] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry described in step (1) is provided by example 2.

[0112] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0113] Application Example 3

[0114] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 3.

[0115] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0116] Application Example 4

[0117] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 4.

[0118] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0119] Application Example 5

[0120] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 5.

[0121] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0122] Application Example 6

[0123] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 6.

[0124] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0125] Application Example 7

[0126] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 7.

[0127] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0128] Application Example 8

[0129] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 8.

[0130] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0131] Application Example 9

[0132] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 9.

[0133] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0134] Application Example 10

[0135] The difference between this application example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by example 10.

[0136] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0137] Application Comparative Example 1

[0138] The difference between this comparative example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by comparative example 1.

[0139] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0140] Application Comparative Example 2

[0141] The difference between this comparative example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by comparative example 2.

[0142] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0143] Application Comparative Example 3

[0144] The difference between this comparative example and application example 1 is that the modified lithium-ion battery cathode slurry in step (1) is provided by comparative example 3.

[0145] The remaining preparation methods and parameters are consistent with those in Application Example 1.

[0146] Performance testing

[0147] The positive and negative electrode sheets provided in Application Examples 1-10 and Comparative Examples 1-3 are used to manufacture pouch cells through processes such as assembly and liquid injection formation.

[0148] The method for manufacturing the negative electrode sheet is as follows: A negative electrode paste is coated onto both sides of an 8µm thick copper foil, with the areal density controlled at 17mg / cm² during the coating process. 2 Meanwhile, a 20mm tab area is reserved on both sides; the coated electrode sheet is passed through a 20-meter-long 110-degree oven at a speed of 3m / s to obtain the negative electrode sheet; the negative electrode sheet is rolled with a roller press, and then laser slitting is used to divide the negative electrode sheet roll into two equal rolls, and finally it is cut into negative electrode sheets of 60cm long and 30cm wide using a mold to complete the production.

[0149] The completed pouch cells were then fitted into fixtures of the appropriate size, and the cells were subjected to a cyclic test at 55°C.

[0150] The battery cells were subjected to a high-temperature storage test at 60°C.

[0151] The test results are shown in Table 1.

[0152] Table 1

[0153]

[0154] analyze:

[0155] The data from Application Examples 1-5 show that by adding an organic sodium source to the positive electrode slurry, the present invention introduces Na ions, which have a larger ionic radius than Li ions, effectively improving the reaction energy level of the positive electrode active material and enhancing the stability of the positive electrode active material under high voltage oxidation-reduction in electrochemical reactions, resulting in excellent cycle and storage performance of the prepared battery cell.

[0156] A comparison of the data results from Application Example 1 and Application Example 6 shows that using tetrasodium ethylenediaminetetraacetate as the sodium source to optimize cell performance is better than using carboxymethyl cellulose as the sodium source.

[0157] A comparison of the data results from Application Example 3 and Application Example 7 shows that using polyacrylonitrile as a binder can better optimize the cycle and storage performance of the battery cell.

[0158] A comparison of the data results from Application Example 1 and Application Examples 8-9 shows that both excessively high and low mixing temperatures can affect the improvement of cell cycle performance and storage performance.

[0159] Comparing the data results of Application Example 5 and Application Comparative Examples 1-2, it can be seen that if the mass fraction of sodium source is too low, the interaction between Na ions and Li ions is weak, and bonding and energy level exchange between the two ions cannot be achieved; if the mass fraction of sodium source is too high, on the one hand, sodium will occupy more Li vacancies, hindering the insertion and extraction of lithium ions, and on the other hand, it will have a certain impact on the crystal structure of the phase, and the energy level and lattice stress will change, thereby affecting the cycle performance of the cell.

[0160] A comparison of the data results from Application Example 5 and Application Comparative Example 3 shows that the cycle performance and storage performance of the battery cell prepared without adding a sodium source are significantly different from those of the battery cell prepared with the modified positive electrode slurry provided by this invention.

[0161] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A modified lithium-ion battery cathode slurry, characterized in that, The positive electrode slurry includes a positive electrode active material, a conductive agent, a sodium source, and a solvent; Based on a dry basis total mass of 100% in the positive electrode slurry, the mass fraction of the sodium source is 2.5-5%; The sodium source is an organic sodium source; the organic sodium source includes tetrasodium ethylenediaminetetraacetate and / or disodium ethylenediaminetetraacetate. The modified lithium-ion battery cathode slurry also includes a binder; the binder is polyacrylonitrile. Based on the total mass of the positive electrode active material, conductive agent, binder, and sodium source being 100%, the mass fraction ratio of the positive electrode active material, conductive agent, binder, and sodium source is (80-90)%:(2-9)%:5%:(2.5-5)%; The positive electrode active material is lithium manganese iron phosphate.

2. The modified lithium-ion battery cathode slurry according to claim 1, characterized in that, The organic sodium source is tetrasodium ethylenediaminetetraacetate.

3. The modified lithium-ion battery cathode slurry according to claim 1, characterized in that, The conductive agent includes any one or a combination of at least two of carbon nanotubes, carbon black, graphene, or conductive graphite.

4. The modified lithium-ion battery cathode slurry according to claim 1, characterized in that, The solvent includes N-methylpyrrolidone and / or N-dimethylformamide.

5. A method for preparing a modified lithium-ion battery cathode slurry as described in any one of claims 1-4, characterized in that, The preparation method includes: The modified lithium-ion battery positive electrode slurry is obtained by mixing the positive electrode active material, conductive agent, organic sodium source and solvent.

6. The preparation method according to claim 5, characterized in that, The mixing temperature is 25-55℃.

7. The preparation method according to claim 5, characterized in that, The mixing order is as follows: (1) The positive electrode active material, conductive agent and sodium source are dry mixed to obtain a dry mixture; (2) Disperse the dry mixture from step (1) in a solvent to obtain the modified lithium-ion battery cathode slurry.

8. The preparation method according to claim 7, characterized in that, The dry mixing in step (1) is performed using a dual planetary dispersion mixer.

9. The preparation method according to claim 7, characterized in that, The dry mixing rate is 1000-2000 pm.

10. The preparation method according to claim 7, characterized in that, The dry mixing time is 15-45 minutes.

11. The preparation method according to claim 7, characterized in that, The dispersion process described in step (2) is accompanied by stirring.

12. The preparation method according to claim 5, characterized in that, The preparation method includes the following steps: (I) The positive electrode active material, conductive agent, binder and sodium source are ball-milled and mixed at 25-55℃ to obtain a dry mixture; The mass fraction ratio of the positive electrode active material, conductive agent, binder and sodium source is (80-90)%:(2-9)%:5%:(2.5-5)%, the dry mixing rate is 1000-2000 rpm, and the dry mixing time is 15-45 min. (II) The dry mixture described in step (I) is dispersed in a solvent to obtain the modified lithium-ion battery cathode slurry.

13. A positive electrode plate, characterized in that, The positive electrode sheet is obtained by coating the modified lithium-ion battery positive electrode slurry according to any one of claims 1-4 onto the current collector and drying it.

14. A lithium-ion battery, characterized in that, The lithium-ion battery includes the positive electrode as described in claim 13.

Citation Information

Patent Citations

  • Preparation method of carbon coated lithium manganese iron phosphate

    CN107768613A

  • Method for preparing lithium manganese iron phosphate by solid-phase coating method

    CN115172718A

  • Magnesium and nickel co-doped lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN115332516A

  • Positive electrode material, preparation method thereof, battery positive electrode and lithium ion battery

    CN110459735A

  • Positive electrode, positive electrode slurry, preparation method and lithium ion battery

    CN114725319A